2009
DOI: 10.1080/10408410802667202
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in shrimp aquaculture: Avenues and challenges

Abstract: As an alternative strategy to antibiotic use in aquatic disease management, probiotics have recently attracted extensive attention in aquaculture. However, the use of terrestrial bacterial species as probiotics for aquaculture has had limited success, as bacterial strain characteristics are dependent upon the environment in which they thrive. Therefore, isolating potential probiotic bacteria from the marine environment in which they grow optimally is a better approach. Bacteria that have been used successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
106
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(110 citation statements)
references
References 201 publications
(228 reference statements)
0
106
0
4
Order By: Relevance
“…To date, improved stress tolerance and immunity by feeding probiotics have been documented in fish [11,24,25], shrimps [26][27][28][29] and molluscs [30,31] however information on probiotic-fed marron under practical transport conditions is not available. The present study evaluated the effect of simulated transport conditions on marron fed the probiotic B. mycoides by measuring intestinal bacterial population, total haemocyte count (THC), bacteraemia, morbidity, dehydration and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…To date, improved stress tolerance and immunity by feeding probiotics have been documented in fish [11,24,25], shrimps [26][27][28][29] and molluscs [30,31] however information on probiotic-fed marron under practical transport conditions is not available. The present study evaluated the effect of simulated transport conditions on marron fed the probiotic B. mycoides by measuring intestinal bacterial population, total haemocyte count (THC), bacteraemia, morbidity, dehydration and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…possess extracellular enzymes amylase and protease [35]. Previous studies reported that the Bacillus bacteria secrete many exoenzymes, such as proteases, carbohydrolases and lipases, which are very efficient in breaking down a large variety of proteins, carbohydrates and lipids into smaller units [36].…”
Section: Resultsmentioning
confidence: 99%
“…Since biofloc technology deals with the bacterial environment, it might also contain some immunostimulatory compounds that are beneficial for the health of cultured organisms. Microorganisms and their cell components have been studied and applied as probiotics or immunostimulants in order to improve the innate immunity and antioxidant status of the shrimp, thereby enhancing their disease resistance (Ninawe and Selvin 2009;Smith et al 2003;Vazquez et al 2009). Even though bioflocs have been confirmed as being the richest source of natural microorganisms and bioactive compounds, little effort was made to study its effect on the physiological health of cultured shrimp, particularly concerning immune and antioxidant defense systems.…”
Section: Immuno-physiological Response By Bioflocsmentioning
confidence: 99%